The establishment of management control within Moroccan public administrations - AZEGAGH , Jalal; ABID , Jihane (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Morocco has embarked on numerous reforms aimed at modernizing public administration, which is subject to the new budget management rules introduced by the organic law of the finance 2016 law inspired by the main principles of New Public Management (New Public Management) who came to propose solutions to remedy the dysfunctions of public management. This approach puts at the center of its priorities the implementation of public management tools and methods, including management control, which appears to be a major function meeting the growing needs of internal management and governance of public administrations and contributes effectively to the improving their performance. The objective of our article is to shed light on the establishment of the management control system within Moroccan public administrations and the constraints related to the specificities of the public sector as well as the success factors of its implementation.